NFATc1 releases BCL6‐dependent repression of CCR2 agonist expression in peritoneal macrophages from Saccharomyces cerevisiae infected mice. Issue 3 (8th January 2016) - Busch, Rhoda; Murti, Krisna; Liu, Jiming; Patra, Amiya K.; Muhammad, Khalid; Knobeloch, Klaus‐Peter; Lichtinger, Monika; Bonifer, Constanze; Wörtge, Simone; Waisman, Ari; Reifenberg, Kurt; Ellenrieder, Volker; et al.
Abstract : In clinical transplantation success of calcineurine inhibitors is overshadowed by increasing rate of opportunistic infections. Here, we show that these inhibitors block the NFATc1/β‐dependent activation of BCL6‐repressed synthesis of CCR2 agonists in macrophages. This results in an impaired mobilization of inflammatory monocytes and in a delayed clearance of yeast infection Abstract : The link between the extensive usage of calcineurin (CN) inhibitors cyclosporin A and tacrolimus (FK506) in transplantation medicine and the increasing rate of opportunistic infections within this segment of patients is alarming. Currently, how peritoneal infections are favored by these drugs, which impair the activity of several signaling pathways including the Ca ++ /CN/NFAT, Ca ++ /CN/cofilin, Ca ++ /CN/BAD, and NF‐κB networks, is unknown. Here, we show that Saccharomyces cerevisiae infection of peritoneal resident macrophages triggers the transient nuclear translocation of NFATc1β isoforms, resulting in a coordinated, CN‐dependent induction of the Ccl2, Ccl7, and Ccl12 genes, all encoding CCR2 agonists. CN inhibitors block the CCR2‐dependent recruitment of inflammatory monocytes (IM) to the peritoneal cavities of S. cerevisiae infected mice. In myeloid cells, NFATc1/β proteins represent the most prominent NFATc1 isoforms. NFATc1/β ablation leads to a decrease of CCR2 chemokines, impaired mobilization of IMs, and delayed clearance of infection. We show that, upon binding to a composite NFAT/BCL6 regulatory element within the Ccl2 promoter, NFATc1/β proteins release the BCL6‐dependent repression of Ccl2 gene in macrophages. These findings suggest a novel CN‐dependent cross‐talk between NFAT and BCL6 transcription factors, which may affect the outcome of opportunistic fungal infections in immunocompromised patients.